Evaluation of Hemodynamic Changes in Retrobulbar Blood Vessels Using Color Doppler Imaging in Diabetic Patients - Gulshan Madhpuriya; Sudheer Gokhale; Alka Agrawal; Prakhar Nigam; Yung-Liang Wan (Life, 2022)
Background—Diabetic retinopathy is a common complication of long-standing hyperglycemia. Microangiopathy-induced retinal changes are well-visualized on ophthalmoscopic examination. However, certain hemodynamic alterations have also been documented in the diabetic population, which have not been completely understood. Aim—To study the hemodynamic changes in retrobulbar circulation in diabetic patients with and without retinopathy, and to compare these changes with non-diabetic controls. Materials and Methods—This hospital-based prospective study included 50 diabetic and 50 non-diabetic patients. The diabetic groups consisted of 25 patients without retinopathy and 25 patients with retinopathy, and were labeled as Groups I and II, respectively. All subjects underwent orbital color Doppler ultrasonography using a linear high-frequency probe. The color Doppler parameters (peak systolic velocity (PSV), end-diastolic velocity (EDV), and resistive index (RI)) were measured and recorded using the spectral waveform of the ophthalmic artery (OA), central retinal artery (CRA), and short posterior ciliary arteries (SPCA). Comparison of obtained values was carried out using appropriate tests of significance. Results—The resistive indices of the ophthalmic, central retinal, and short posterior ciliary arteries were significantly higher in diabetic patients compared to controls (p < 0.001). The difference was also significant between Group I and Group II. Comparison of PSV and EDV of CRA and SPCAs among three groups using one-way ANOVA revealed a significant difference, with the highest blood flow velocities in the control group and the lowest in diabetics with retinopathy. The ophthalmic artery showed no significant change in blood flow velocity. Analysis using the Pearson correlation coefficient provided a positive correlation between the RI values of OA, CRA, and SPCA and the presence of diabetic retinopathy (OA = r 0.417, p < 0.001; CRA = r 0.466, p < 0.001; SPCA = r 0.438; p < 0.001). Conclusions—The resistive index of OA, CRA, and SPCA is a reliable indicator to assess diabetic-associated hemodynamic changes. The use of orbital color Doppler ultrasonography in diabetic patients can help in the identification of patients who are at risk of developing retinopathy.